PROFILE OF SOFTWARE/APPLICATION PRODUCTS DEVELOPED IN STRICTO SENSU GRADUATE NURSING PROGRAMS: CROSS-SECTIONAL STUDY. - da Silva, Sara Soares Ferreira; de Paula, Danielle Galdino; dos Santos, Inês Maria Meneses; de Carvalho Queluci, Gisella (Online Brazilian Journal of Nursing)
Objective: To analyze the profile of software and application products created in stricto sensu Graduate Nursing Programs in the biennium 2021-2022. Method: This is a descriptive study with a quantitative approach. Primary data made available by the Coordination for the Improvement of Higher Education Personnel categorized as belonging to the basic area of Nursing and registered in 2021 and 2022 were used. A total of 75 software/application products were included and analyzed according to consolidated criteria of technical/technological products. Bivariate analysis was performed using Fisher's exact test, adopting a p value below 0.05. Results: The profile evidenced was of products developed in public institutions, located in the Southeast region, and within master's programs. Moreover, among the 16 identified target areas, pediatrics, management, and primary health care stood out. Patients, nurses, and the multidisciplinary team were the main target audience. The products were mostly classified as highly innovative, with real impact and high complexity. Conclusion: Stricto sensu graduate nursing programs foster the creation of software and applications with thematic variability and a diverse target audience. The findings highlighted the great potential of nursing and public education for technological development aimed at improving health care delivery.